Presentation of anthology "Uryankhay. Tyva Depter” in Tuva - Lamazhaa, Anna M. (The New Research of Tuva, 2010)
Review of the solemn presentation of anthology "Uryankhay. Tyva Depter” (Moscow, 2007-2009) with participation of the anthology’s compiler S.K. Shoygu that was held on September, 27 2010 in the State Theatre of Music and Drama, Kyzyl.
Keywords: S. K. Shoygu; presentation; anthology; Uryankhay; government; Music and Drama Theatre; meeting